Green hydrogen generation from petrochemical wastewater - Khan, Maksudur Rahman; Thurga Devi, Munusamy; Chin, Sim Yee (2021)
The worldwide energy demand is expanding and demand for pure hydrogen is estimated around 70 Mt annually. This hydrogen currently is produced from 6% of global natural gas use and 2% of coal comsumption, responsible for CO2 emissions up to 830 Mt per year. Requirement for green hydrogen and alternative to conventional hydrogen production technologies are in need where photocatalytic pathway could be great choice. Most of the study uses noble metal as the co-catalyst but it is impractical to be used in large scale owing to high price. Majority of light sources used in the photocatalytic system are Xenon or Halogen lamp leading to huge heat dissipation. The focal point of present invention is fabrication of noble metalfree carbon doped exfoliated g-C3N4 photocatalyst and usage in dual processess of hydrogen production and wastewater treatment under LED light irradiation.